Communicative Methods of Teaching French Language at University - Subkhanovna, Mardanova Firuza (Research Parks Publishing LLC, 2022)
The communicative method is aimed primarily at active interaction between the teacher and the student of a foreign language. Particular attention is paid to the independent work of students in pairs and micro-groups. All kinds of situations are created so that students can try themselves in real communication. This makes it possible to learn how to spontaneously express your thoughts. By discussing various topics and problems in groups, students do not just speak, they learn to “think in a foreign language”